External focus of attention affects shot accuracy in elite archers - Vrbik, A.; Zavoreo, I.; Vrbik, I. (Acta Kinesiologica, 2021)
The intention of this study was to find out if external focus of attention, steering the archers` focus on distal movement effects, will provide better shooting accuracy expressed as higher number of 10 pointsand higher overall result. The subject sample was consisted of 10 elitemale archers, with average age 25.8 years. The sample of variables was derivedfrom observed characteristics of entities in different shooting conditions. A measure of arrow distance from the center of the target face was usedin order to estimate shooting precision.The testing consisted of three different shooting conditions: C1-free focus of attention, C2 -internal focus of attention and C3 -external focus of attention. The analysis showed that the highest results were obtained in condition of externally oriented focus of attention (C3), and the lowest results in condition of internally oriented focus of attention (C2). Friedman`s ANOVA did not show statistical differences betweenthe conditions, but they were found between C2 and C3 in afterwards administered Wilcoxon`s test (p=0.047).